EVALUATION OF THE IMPLEMENTATION OF WASTE GENERATION REDUCTION INTO COMPOST WITH WINDROW SYSTEM IN THE TALANG GULO FINAL PROCESSING, JAMBI CITY - Mega Muitiara Sari; Andra Puput Marya Ani; I Wayan Koko Suryawan (Universitas Lambung Mangkurat, 2022)
Talang Gulo Final Processing Site, Jami City will make efforts to reduce biodegradable waste consisting of leaf waste. The processing process that can be applied is by converting it into compost with an aerobic process with a windrow system. The purpose of this study was to evaluate the composting system and the results of existing waste processing. This research was conducted by direct observation and secondary data collection from the local management inventory. The composition of biodegradable waste in Jambi City consists of 47.4% food waste and 2.1% garden waste. However, the application of food waste is quite difficult to handle because of its characteristics, therefore garden waste is a priority for reduction by the government. The results of monitoring for one month in a row mean that the waste entering the compost facility is 4086 kg/day. The percentage of waste reduction from composting activities in total can be 0.986% of the total waste generation of Jambi City, or 45.426% of the total waste generation of Jambi City's gardens. The final measurement results of compost have met the quality standard of SNI 19-7030-2004 which has been set by the Indonesian government. The value of water content, pH, C – Organic, N – Total, C/N, P2O3, and K2O Total is 13.64%; 7,12; 4.77%; 0.42%; 11.4% 45.01%; and 0.25%, respectively. It is hoped that even though the achievement of waste reduction from this activity is still low, if it is seen from the opportunities for sustainable management and social support from the community and the government, it will reduce waste generation in Jambi City.